Bantuan Benih Unggul Dan Pelatihan Membuat Susu Kedelai - Sumarmi, Sumarmi; Triyono, Kharis (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2019)
Increasing soybean production is still experiencing many obstacles. Senting village farmers, Sambi sub-district, Boyolali district, used to grow soybeans with seeds purchased from local village markets of poor quality. Given that the importance of seeds in influencing soybean yields, farmers need to be supported the help of superior seeds. The seeds for farmers' help are intended to show that new varieties of soybeans will produce higher yields. Community service is complemented by training in making soymilk for PKK mothers in the local village. The output of community service in 2019 is expected to be able to show an increase in crop yields and be useful for mothers to generate ideas and be brave in developing soy milk. Students who help this service are expected to learn directly from the community and also on soybean farms.